2017
DOI: 10.1111/1540-6229.12209
|View full text |Cite
|
Sign up to set email alerts
|

Big‐Box Stores and Urban Land Prices: Friend or Foe?

Abstract: This study examined the effect of a new Walmart store on nearby U.S. urban land prices and found that, within one quarter mile of a new Walmart store locale, land prices increased by almost 39% over the four‐year development time period. Supercenters and commercial land sales were instrumental in driving the positive price effects. Robustness tests found a positive land price effect with other big‐box stores, suggesting that the land price effect was not limited to Walmart stores, but in fact, was a big‐box st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 47 publications
0
15
1
Order By: Relevance
“…Moreover, Shopping's accessibility increased due to its physical integration with the terminal metro and bus station ( Vilarinho Station). Pope and Pope (2015) and Slade (2018) also found positive land premium derived from the proximity to large‐scale retail, in the case of Walmart and big‐box stores in many metro areas in the US.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, Shopping's accessibility increased due to its physical integration with the terminal metro and bus station ( Vilarinho Station). Pope and Pope (2015) and Slade (2018) also found positive land premium derived from the proximity to large‐scale retail, in the case of Walmart and big‐box stores in many metro areas in the US.…”
Section: Discussionmentioning
confidence: 95%
“…We have not been able to find any information about rental rates for commercial properties in Swedish municipalities. However, the recent study by Slade () showed that land prices within one quarter mile of a new Wal‐mart store increased by almost 39% over a four‐year development time period. The positive effects were found to dissipate with distance from the new store, suggesting that the Wal‐mart effect is highly localized.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the effects of large retailers on property values have been largely left unexplored, and the results from the few previous studies that have focused on this relationship are ambiguous. While some find positive effects of large establishments on property values (Sirpal 1994; Pope and Pope 2015; Van Fossen 2017; Slade 2018), others find negative effects (Corlija, Siman, and Finke 2006; Johnson et al 2009), and some find no effects at all (Loyer 2010). Consequently, we still lack knowledge on whether big‐box retail entry increases the long‐term attractiveness of the place.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the more recent studies also fail to control for spatial and temporal heterogeneity, and the results they observe––or parts of it––may be driven by a potential omitted variable bias. Some notable exceptions are Pope and Pope (2015) and Slade (2018), who found positive results of large retail entry on property values when using a difference‐in‐difference model and conducting the analysis at a more disaggregated geographical level. However, both of these studies investigate the effects when Walmart entered local markets in the United States, offering no insights for the effects of other type of retailers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation